Soviet Home Army, Its Strategy and Tactics in 1944–1953 - Starkauskas, Juozas (Genocidas ir rezistencija, 1997)
There are several reasons for a closer examination of the functioning of the various types of NKVD–MVD–MGB troops in Lithuania. One of them is this: in 1950s and 1970s, historians and publicists, inspired by the Communist Party and the KGB, began to claim that the “armed bourgeois nationalist gangs” had been crushed by the so–called people’s defenders, popularly known as the stribai (i.e. destruction battalions). It is therefore necessary to prove who fought against whom in Lithuania in 1944–1953 and what the role of these formations was in destroying the Lithuanian freedom fighters – the partisans. Finally, it was necessary to understand the tactics and principles of operation of the chekist army and its relations with chekist operatives to enable to turn another page of history. The behaviour, methods, and relations of the internal army with other repressive structures.